1995
DOI: 10.1128/aac.39.5.1045
|View full text |Cite
|
Sign up to set email alerts
|

Interaction study of lomefloxacin and ciprofloxacin with omeprazole and comparative pharmacokinetics

Abstract: To assess whether or not concomitant omeprazole treatment influences the pharmacokinetics of lomefloxacin and ciprofloxacin, a randomized, double-blind four-way-crossover study was performed. Another objective was to compare the pharmacokinetics of lomefloxacin and ciprofloxacin. Twelve healthy volunteers participated. On days 1 to 4 of each study period, each of them took 20 mg of omeprazole or a placebo orally, and on day 4, each took 400 mg of lomefloxacin or 500 mg of ciprofloxacin orally. Blood and urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Co-administration of trovafloxacin and omeprazole reduced the AUC for trovafloxacin by 18% and the C max by 32% [12]. On the other hand, both AUC 0-∞ and C max for lomefloxacin showed small increases (5-8%) when given with omeprazole [21]. However, none of these changes are considered to be clinically important, and there are no recommendations to alter the dose of fluoroquinolones in the presence of omeprazole.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Co-administration of trovafloxacin and omeprazole reduced the AUC for trovafloxacin by 18% and the C max by 32% [12]. On the other hand, both AUC 0-∞ and C max for lomefloxacin showed small increases (5-8%) when given with omeprazole [21]. However, none of these changes are considered to be clinically important, and there are no recommendations to alter the dose of fluoroquinolones in the presence of omeprazole.…”
Section: Discussionmentioning
confidence: 85%
“…Both AUC 0-∞ and C max for ciprofloxacin decreased by 15-16% when administered with omeprazole [21]. Co-administration of trovafloxacin and omeprazole reduced the AUC for trovafloxacin by 18% and the C max by 32% [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, in vitro studies have demonstrated that enoxacin, cimetidine, ranitidine, and famotidine dissolution and availability for absorption in simulated gastric juice and simulated intestinal fluid are mutually reduced for all three enoxacin-histamine H 2 -receptor antagonist pairings [88]. Omeprazole has also not been shown to alter the pharmacokinetics of quinolones to a clinically-significant degree [56,[101][102][103]. Thus, these agents can be recommended as alternative noninteracting antiulcer and antiesophagitis therapy.…”
Section: Absorption Interactionsmentioning
confidence: 98%
“…Omeprazole, a proton-pump inhibitor frequently prescribed for patients with peptic ulcers or other gastric acid-related conditions, has resulted in small changes in fluoroquinolone pharmacokinetics. 132,133 In theory, omeprazole interacts with other drugs by altering absorption due to decreasing gastric acid, altering clearance through occupying the CYP metabolic pathway, or competing for renal excretion. Thus, the impact of omeprazole on gemifloxacin pharmacokinetics was evaluated in a randomized, doubleblind, crossover study of 12 adult healthy male volunteers.…”
Section: Drug Interactionsmentioning
confidence: 99%